Delegated and implementing acts in the proposal of “hydrogen and decarbonized gas market package” – meaning and functioning - Kruś, Maciej; Krzanowski, Marcel (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The European Commission presented two proposals on 15 December 2021 with the objective of reforming the internal gas market by introducing hydrogen and decarbonized gases. The main objective of the paper is to present the legal characteristics of the delegated and implementing acts provided in the provisions of these proposals from the point of view of the theory of administrative law. On this basis, we shall attempt to assess their importance in shaping the regulations for biomethane and hydrogen. This objective will be achieved by outlining the assumptions of these proposals, briefly presenting the delegated and implementing acts provided for in them and analysing the nature of these acts, including the differences between them and the effects of their adoption.
Keywords: delegated act; implementing act; tertiary acts; EU administrative law; EU administrative acts